Socio Cultural Dynamics and Double Precarity from the DIY Music Scene in Purwokerto, Indonesia - Rizkidarajat, Wiman; Mutahir, Arizal; Chusna, Aidatul; Saadah, Kholifatus (Bina Nusantara University, 2025)
The research explores the socio-cultural dynamics and double precarity faced by Voicehell, a do-it-yourself (DIY) music scene based in Purwokerto. It provides an in-depth examination of the intersecting forms of precarity experienced by a collective of young people, conceptualized as an intermediate generation navigating their life choices within the broader context of the global risk generation. Using a qualitative method combined with a biographical approach, the research presents a reflective biography of the youth involved with Voicehell. The findings reveal that the collective negotiates various manifestations of capital, which may undermine their authenticity and authority as a DIY music scene. Notably, the research does not present a simplistic account of Voicehell's challenges. Instead, it demonstrates that their distinctive position within both a provincial city and the broader Indonesian context exposes them to double precarity. The research further illustrates how such conditions may also affect other Indonesian youth groups, as well as those in the Global North, where collectives frequently contend with spatial inadequacies rooted in underdeveloped socio-economic contexts. These structural limitations sustain their position within the global risk generation. By analyzing the case of Voicehell, the research contributes to a deeper understanding of youth cultures and their negotiation of authenticity, authority, and precarity in a globalized world.